A.N. Schmidt: A Mystical Correspondent of the Philosopher V.S. Solovyov - V. Kravchenko, Victoria (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the phenomenon of the personality of A.N. Schmidt, a modest journalist from Nizhny Novgorod, who gained initial fame through her correspondence with the outstanding Russian philosopher V.S. Solovyov. However, Schmidt was the original novelist, the author of religious and mystical writings, whose considerable influence on many figures of Russian spiritual culture of the twentieth century is increasingly found in in-depth studies of this era. Modern receptions of Schmidt’s creativity demonstrate the relevance of her ideas and need an adequate religious and mystical interpretation.